Assessment of state support of agriculture of Ukraine - Zakharova, Natalia; Захарова, Наталя Юріївна; Захарова, Наталья Юрьевна (My University, 2020)
The agricultural sector of Ukraine's economy forms more than 10% of the country's GDP, and the share of agricultural products in the total structure of exports is 44.3%. This sector determines the potential of other sectors of the economy and forms the basis of food security. Despite this, due to a number of factors, among which we should highlight, first of all, high dependence on climatic conditions and seasonality of production, agriculture needs support from the state.
Keywords: agricultural sector; food security; food markets